(untitled) (Research, Society and Development, 2022)
Obesity can be defined as the accumulation of excess body fat to the point of compromising the health of individuals affected by it, in addition to being a risk factor for the development of other pathologies such as diabetes, dyslipidemia, cardiovascular and respiratory diseases. Thus, the illness of the population entails expenses for public health, since the use of medicines and treatments is necessary. In this context, this work aims to expose the dangers attributed to obesity, as well as its impact on public health, analyzing its costs. To this end, an integrative literature review was carried out in a time frame from 2018 to 2022, obtaining results that generated discussion about the theme. It was found that the growing rate of obesity cases is potentially due to changes in eating habits over the years, as well as the growth of the food industry and that, with this increase in cases, the public health system has been burdened. Therefore, disease prevention practices, such as the adoption of good eating habits, physical activity and nutritional education are seen as necessary to reduce such costs in public management.